Fuzzy Control of Yaw and Roll Angles of a Simulated Helicopter Model Includes Articulated Manipulators - Hossein Sadegh Lafmejani; Hassan Zarabadipour (IAES Indonesian Section, 2013)
Fuzzy logic controller (FLC) is a heuristic method by If-Then Rules which resembles human intelligence and it is a good method for designing Non-linear control systems. In this paper, an arbitrary helicopter model includes articulated manipulators has been simulated with Matlab SimMechanics toolbox and then we designed a fuzzy controller for its yaw and roll angles when the manipulators are moving for a task. Results reveal that a simple FLC can control this complex system well.